A Study on Student Attitudes in Learning Programming using Physical Computing - Zuraini Hanim Zaini; Noreen Izza Arshad; Balbir SM Singh; Nurshazlyn M Aszemi; Subuh Anggoro; Santhy Hawanti (Universitas Muhammadiyah Purwokerto, 2020)
Learning to program can be difficult for the students. Students must master language syntax, programming theory, and problem-solving techniques. Efforts have been made to assist students in understanding how to program. This study is intended to examine whether Arduino, as a teaching and learning tool, helps in generating students’ interests towards programming. Arduino is one of the physical computing tools which has an open-source electronics platform based on user-friendly hardware and software for creating different projects and applications. Arduino is easy to be used by beginners, yet flexible enough for advanced users to learn physical computing and programming. This study adopted a quantitative research method to measure the student’s attitude in learning programming using physical computing. The sample of this study is 56 students from the foundation program and undergraduate program. To gauge students’ perception, students’ attitude survey was adapted. The collected data were analyzed using descriptive analysis. Based on the analysis, the study found that the overall mean score was 4.253. The result indicated that student has a positive attitude in learning programming using physical computing.